Differences in Tolerance to Host Cactus Alkaloids in Drosophila koepferae and D. buzzatii - Soto, Ignacio M. (Public Library of Science, 2014)

(untitled)
The evolution of cactophily in the genus Drosophila was a major ecological transition involving over a hundred species in the Americas that acquired the capacity to cope with a variety of toxic metabolites evolved as feeding deterrents in Cactaceae. D. buzzatii and D. koepferae are sibling cactophilic species in the D. repleta group. The former is mainly associated with the relatively toxic-free habitat offered by prickly pears (Opuntia sulphurea) and the latter has evolved the ability to use columnar cacti of the genera Trichocereus and Cereus that contain an array of alkaloid secondary compounds. We assessed the effects of cactus alkaloids on fitness-related traits and evaluated the ability of D. buzzatii and D. koepferae to exploit an artificial novel toxic host. Larvae of both species were raised in laboratory culture media to which we added increasing doses of an alkaloid fraction extracted from the columnar cactus T. terschekii. In addition, we evaluated performance on an artificial novel host by rearing larvae in a seminatural medium that combined the nutritional quality of O. sulphurea plus amounts of alkaloids found in fresh T. terschekii. Performance scores in each rearing treatment were calculated using an index that took into account viability, developmental time, and adult body size. Only D. buzzatii suffered the effects of increasing doses of alkaloids and the artificial host impaired viability in D. koepferae, but did not affect performance in D. buzzatii. These results provide the first direct evidence that alkaloids are key determinants of host plant use in these species. However, the results regarding the artificial novel host suggest that the effects of alkaloids on performance are not straightforward as D. koepferae was heavily affected. We discuss these results in the light of patterns of host plan evolution in the Drosophila repleta group.